Structural Design and Sealing Performance Analysis of Biomimetic Sealing Ring - Chuanjun Han; Han Zhang; Jie Zhang (Applied Bionics and Biomechanics)
In order to reduce the failure probability of rubber sealing rings in reciprocating dynamic seal, a new structure of sealing ring based on bionics was designed. The biomimetic ring has three concave ridges and convex bulges on each side which are very similar to earthworms. Bulges were circularly designed and sealing performances of the biomimetic ring in both static seal and dynamic seal were simulated by FEM. In addition, effects of precompression, medium pressure, speed, friction coefficient, and material parameters on sealing performances were discussed. The results show that von Mises stress of the biomimetic sealing ring distributed symmetrically in no-pressure static sealing. The maximum von Mises stress appears on the second bulge of the inner side. High contact stress concentrates on left bulges. Von Mises stress distribution becomes uneven under medium pressure. Both von Mises stress and contact stress increase when precompression, medium pressure, and rubber hardness increase in static sealing. Biomimetic ring can avoid rolling and distortion in reciprocating dynamic seal, and its working life is much longer than O-ring and rectangular ring. The maximum von Mises stress and contact stress increase with the precompression, medium pressure, rubber hardness, and friction coefficient in reciprocating dynamic seal.